QUANTUM TEACHING MATERIALS TO IMPROVE COGNITIVE LEARNING OUTCOMES ASSISTED BY CHOOSING NUMBERS ON STATIC ELECTRICITY MATERIAL - Asri Fadhila; M. Rahmad; Zulhelmi Zulhelmi (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Examining the effects of Choose Number-assisted Quantum Teaching on students' cognitive learning outcomes is the goal of this study. The participants in this research were Darul Hikmah Pekanbaru class IX MTs students. Quasi Experimental Design with Posttest-Only Control Design is the research design used in this type of study. Research tools for cognitive learning outcomes that employ objective assessments. Both inferential analysis and descriptive analysis were used to examine the study's findings. Descriptive analysis revealed that when students used Quantum Teaching with Choose Number support, their average cognitive learning results improved. There was a substantial change in the cognitive learning outcomes of students following the implementation of quantum teaching, despite the fact that the data were inferentially examined using the t-test using independent sample t-test technique.